GERAKAN PENGUATAN LITERASI MEMBACA DAN MENULIS UNTUK MENINGKATKAN KOMPETENSI DASAR SISWA DI DESA KADUARA TIMUR PRAGAAN SUMENEP - Afifah, Muru'atul; Revina, Revina (Universitas Al-Amien Prenduan, 2024)
The community service activity themed “Movement to Strengthen Reading and Writing Literacy to Improve Basic Competencies of Students in Kaduara Timur Village, Pragaan, Sumenep” was carried out in response to the low basic literacy skills of students in rural areas. Based on initial observations, it was found that most students still had difficulty understanding reading materials and writing simple sentences effectively. This was due to the lack of literacy activities at school and the lack of a conducive learning environment at home. To address these issues, the outreach team carried out a series of activities, including interactive reading training, creative writing coaching, and the provision of community-based reading corners. The community service methods used included a participatory approach through workshops, coaching clinics, and daily literacy habits involving teachers and parents. The results of these activities showed a significant improvement in students' reading comprehension and simple writing skills. In addition, there was new enthusiasm from teachers to continue the literacy program independently by integrating it into daily learning activities. This movement also raised community awareness of the importance of literacy culture as the foundation for character building and 21st-century skills. Thus, the strengthening of reading and writing literacy in Kaduara Timur Village has successfully become an effective and sustainable model of community-based educational empowerment.